Ultrasonic Velocity, Viscosity and Density of 2-Hydroxy Acetophenones in Ethanolic Solution at 303.15 K - Ubale, Sanjay; Palaskar, N.G.; Farooqui, Mazahar; Pardeshi, R.K.; Lande, M.K. (Asian Journal of Chemistry, 2010)
Density, ultrasonic velocity and relative viscosity of 2-hydroxy acetophenone in ethanolic solutions have been measured as a function of electrolyte concentration at 303.15 K. The experimental data is used to calculate molar volume, apparent molar compressibility etc. These parameters are used to interpret the solvent-solvenl, ionsolvent and solute-solvent interactions.